2021
DOI: 10.1002/adhm.202001761
|View full text |Cite
|
Sign up to set email alerts
|

The Blanket Effect: How Turning the World Upside Down Reveals the Nature of Graphene Oxide Cytocompatibility

Abstract: Extensive cytocompatibility testing of 2D nanocarbon materials including graphene oxide (GO) has been performed, but results remain contradictory. Literature has yet to account for settling—although sedimentation is visible to the eye and physics suggests that even individual graphenic flakes will settle. To investigate settling, a series of functional graphenic materials (FGMs) with differing oxidation levels, functionalities, and physical dimensions are synthesized. Though zeta potential indicates colloidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…The most impressive feature we noted in our experiments is the peculiar appearance of the cells growing under the supports, even if it is relatively common to observe cells attached under the glass slides. Indeed, the growth of cells under the supports was previously observed using the inverted cell culture [35], transwell assay [36], and ceiling culture methods [37]. Moreover, in accordance with our observations, the inverted culture method was also previously employed to grow mouse primary hippocampal neurons showing an improved neurogenesis process and an increment in cell survival in this condition.…”
Section: Discussionsupporting
confidence: 85%
“…The most impressive feature we noted in our experiments is the peculiar appearance of the cells growing under the supports, even if it is relatively common to observe cells attached under the glass slides. Indeed, the growth of cells under the supports was previously observed using the inverted cell culture [35], transwell assay [36], and ceiling culture methods [37]. Moreover, in accordance with our observations, the inverted culture method was also previously employed to grow mouse primary hippocampal neurons showing an improved neurogenesis process and an increment in cell survival in this condition.…”
Section: Discussionsupporting
confidence: 85%
“…As pointed out earlier, [2][5] [6] the series converges rapidly for large values of {τ, α}, but slowly for small values. A large number of terms for the series (e.g., > 100000) might be evaluated and added to the final result in the hope of reaching convergence, as was done by Holt et al [5]. However, it was found in the present work using standard double precision floating-point arithmetic that the factor exp (−αm 2 π 2 τ )m…”
Section: Infinite-series Solution (Iss)mentioning
confidence: 92%
“…Very recently, Holt et al used the analytic solution in their work on the rôle of nanoparticle sedimentation in cytotoxicity studies. [5] They reported that they needed to numerically sum a great number of terms (over 10 5 ) in the expression by M&W to obtain satisfactory results, but did not give further details. Here, the numerical evaluation of the expressions derived by Mason & Weaver is further investigated over a wide range of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies, and results from other research groups, clearly demonstrated that graphene oxide (GO) fulfilled most of the conditions required for enzyme immobilization support, that is, it bound the protein with high yield, and did not decrease catalytic activity, even after storage or lyophilization 1–3 . It is of a great importance that this material is cytocompatible and exerts no toxic effects on cell viability 4,5 . In the case of enzymes as adenylate kinase (AK), expected to act in extracellular environment, GO seems to be the most convenient support preventing the cellular internalization of AK‐GO system 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It is of a great importance that this material is cytocompatible and exerts no toxic effects on cell viability. 4,5 In the case of enzymes as adenylate kinase (AK), expected to act in extracellular environment, GO seems to be the most convenient support preventing the cellular internalization of AK-GO system. 6 The preliminary in vitro evaluation confirmed the positive effect of AK-GO nanobiocatalyst on the cultured cells, especially when exposed to high, cytotoxic ATP concentrations.…”
Section: Introductionmentioning
confidence: 99%